Lucilia sericata (Meigen) and Chrysomya megacephala (Fabricius) (Diptera: Calliphoridae) Development Rate and its Implications for Forensic Entomology - Kapil Verma; Reject Paul (Wolters Kluwer Medknow Publications, 2016)
Forensic entomology is basically a science that is based on the scientific study of the invasion and succession pattern of arthropods with their developmental stages of different species found on the decomposed cadavers during legal investigations. The developmental rate of Lucilia sericata and Chrysomya megacephala was studied in beef liver for the correlation of time duration in each phase with the temperature and climate. The obtained data belong to L. sericata at temperatures between 22°C and 26°C (mean - 24°C) and relative humidity 50% ±10% and C. megacephala at temperatures between 23°C and 27°C (mean - 25°C) and relative humidity 55% ±10%. From the analysis of results, it was observed that in the climatic conditions of the study area, time since death assessment involving L. sericata was found to be with a potential of maximum 10-11 days and C. megacephala with 8-9 days. The data emerged as results from the present work would be beneficial for investigations involving decomposed dead body remains for the assessment of time since death.